PEMANFAATAN PEKARANGAN RUMAH UNTUK TANAMAN HOLTIKULTURA SEBAGAI STRATEGI WIRAUSAHA KREATIF BAGI MASYARAKAT KELURAHAN SANDBILIK - Rati Pundissing; Chrismesi Pagiu; Dian Intan Tangkeallo; Dwibin Kannapadang (Yayasan Education and Social Center, 2021)
Real Work Lecture or abbreviated as KKN is a form of community service activities carried out by students guided by one of the guidance lecturers with a cross-scientific and sectoral approach at certain times and regions. This KKN activity aims to 1) KKN during this pandami period is a form of UKI Toraja's contribution to prevent the transmission of Covid-19 in the community with the aim of implementing KKN to make the role of students as part of the community in helping the social government to socialize and implement health protocols to prevent the spread of Covid-19. 2) as a medium of learning and fostering a sense of student concern for the problems faced by the community and reminding the public to remain active in improving the economy during the pandemic. This KKN activity is based on one core program in agriculture, namely